A Cross-Sectional Analysis of Dissociation, Loneliness, And Self-Esteem Among Young Adults - Jaiswal, Varsha; Srivastava, Kiran (Journal of Neonatal Surgery, 2025)
The years between 18 and 25 are known as emerging adulthood, and they are characterised by substantial social and psychological shifts. In the recent study, one hundred young adults of both sexes took part in order to investigate the connections between dissociation, self-esteem, and loneliness. A recent study involved one hundred young adults of varying genders to examine the links between dissociation, self-esteem, and feelings of loneliness. To investigate these connections, researchers utilized the Rosenberg Self-Esteem Scale (RSES), the UCLA Loneliness Scale, and the Dissociative Experiences Scale (DES). The results confirmed a significant negative correlation between dissociation and self-esteem (r = -.41, p < .01), as well as a moderate positive correlation between dissociation and loneliness (r = .28, p < .05). The analysis indicated that loneliness did not act as a mediator between dissociation and self-esteem (β = .07, p = .22). These findings emphasize the significance of emotional bonds and self-worth in understanding incidents of dissociation. The significance of gender- sensitive mental health interventions that emphasize trauma processing and self-worth is underscored by these findings. The small group of participants and the use of self-reported data only, which can be influenced by the respondent and memory biases, are some of the limitations.